Social Development in Sungai Kakap Village (Study on Social Change and Development) - Iwan Ramadhan; Daniel Daniel (LPPM Universitas PGRI Sumatera Barat, 2021)
The problems that often arise in village development are the low of welfare and quality of people’s life in the village; lack of desire of the stakeholders to accelerate the development itself; as well as village governance that requires adjustment to the mandate of Law Number 14 of 2014 concerning Villages. Therefore, village development needs to have proper planning and management, so the village can be developed properly. In this case, there is a need for sustainable planning and development that fit of planning and programs that have been prepared in order to optimize the potential of natural resources, human resources, and science and technology. By matching and combining the three components, it is hoped that these three aspects can run well. and can be sustainable. The method used in this research was descriptive qualitative research method. The expected objectives of this research were to find out the existing development programs in Sungai Kakap village, investigate what facilities are available there, and community empowerment programs implemented. It was also to find out the social changes that have occurred in Sungai Kakap village due to the development that occurred there.